The influence of intrinsic motivation and work life balance on organizational citizenship behavior with organizational commitment as an intervening variable at West Semarang KPP - Trisni Saraswati; Indarto Indarto; Yuli Budiati (Sean Institute, 2024)
This research focuses on the West Semarang Tax Service Office, a vertical work unit that works in parts of Central Java and is overseen by the Central Java I Regional Office of the Directorate General of Taxes. This study investigates the impact of work-life balance and intrinsic motivation on organizational citizenship behavior at KPP West Semarang, using organizational commitment as an intervening variable. The study's sample consisted of ninety respondents who were deemed to be representative of the entire population. The sample approach employed in this study is known as purposeful sampling, or sampling based on criteria or characteristics. These standards and factors consist of: Employees of KPP Pratama in West Semarang who have been employed there for a minimum of five years, have an ASN and are prepared to take part in the survey. using data analysis software called smartpls. The results of the test show that intrinsic motivation and work-life balance positively affect organizational commitment. Further research revealed that inner desire, work-life balance, and organizational commitment all had a favorable influence on organizational citizenship behavior. In the mediation effect test, it was discovered that organizational commitment moderated the relationship between intrinsic motivation and organizational citizenship behavior. Furthermore, organizational commitment can lessen the negative effects of work-life balance on organizational citizenship behavior.